2006
DOI: 10.1007/s10549-005-9151-2
|View full text |Cite
|
Sign up to set email alerts
|

XPD Common Variants and their Association with Melanoma and Breast Cancer Risk

Abstract: There are suggestions in the literature that common variants in the XPD gene may be associated with an altered risk of melanoma and breast cancer. To establish if the XPD common variants Asp312Asn and Lys751Gln are associated with an increased melanoma or breast cancer risk we performed an association study based on genotyping 426 unselected patients with malignant melanoma (MM) and 1830 consecutive breast cancer cases and compared the results to 1262 geographically matched newborns, 621 adults from the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 24 publications
3
26
1
2
Order By: Relevance
“…Justernhoven et al (2004) observed that ERCC2 Lys751Gln CC (OR = 3.69, 95% CI = 1.76-7.74) was one risk genotype for breast cancer, and ERCC2 Asp312Asn G/Lys751Gln C was the most potent riskconferring haplotype for breast cancer (OR = 3.49, 95% CI = 2.30-5.28) in a German population. Debniak et al (2006) demonstrated a modest association with breast cancer risk when the ERCC2 Lys751Gln CC/Asp312Asn AA genotype (OR = 1.5, P \ 0.05) segregated together in a Poland population. In a Finnish Caucasian population, Mestsola et al (2005) reported a significant increase in breast cancer risk among women who had ever smoked if they carried the ERCC2 Lys751Gln Gln/Gln genotype (OR = 2.52, 95% CI = 1.27-5.03, P = 0.011), compared with women who smoked but did not carry these genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Justernhoven et al (2004) observed that ERCC2 Lys751Gln CC (OR = 3.69, 95% CI = 1.76-7.74) was one risk genotype for breast cancer, and ERCC2 Asp312Asn G/Lys751Gln C was the most potent riskconferring haplotype for breast cancer (OR = 3.49, 95% CI = 2.30-5.28) in a German population. Debniak et al (2006) demonstrated a modest association with breast cancer risk when the ERCC2 Lys751Gln CC/Asp312Asn AA genotype (OR = 1.5, P \ 0.05) segregated together in a Poland population. In a Finnish Caucasian population, Mestsola et al (2005) reported a significant increase in breast cancer risk among women who had ever smoked if they carried the ERCC2 Lys751Gln Gln/Gln genotype (OR = 2.52, 95% CI = 1.27-5.03, P = 0.011), compared with women who smoked but did not carry these genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the power of statistical analysis can be substantially increased by assuming linked loci. However, only 23% of the reviewed studies identified different potent risk-conferring haplotypes (9,(28)(29)(30) and explored the role of these haplotypes on cancer susceptibility. The sample size for each haplotype is too small for meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…After screening the titles and abstracts, only 20 potentially eligible articles were identified for further detailed evaluation. After full-text assessment of these articles, we included a total of 15 articles (Dybdahl et al, 1999;Winsey et al, 2000;Vogel et al, 2001;Yin et al, 2003;Baccarelli et al, 2004;Lovatt et al, 2005;Festa et al, 2005;Han et al, 2005;Thirumaran et al, 2006;Li et al, 2006;Millikan et al, 2006;Debniak et al, 2006;Povey et al, 2007;Kertat et al, 2008;Paszkowska-Szczur et al, 2013) in this meta analysis, including 9 studies for cutaneous melanoma (Winsey et al, 2000;Baccarelli et al, 2004;Han et al, 2005;Li et al, 2006;Millikan et al, 2006;Debniak et al, 2006;Povey et al, 2007;Kertat et al, 2008;Paszkowska-Szczur et al, 2013), 7 studies for basal cell carcinoma (Dybdahl et al, 1999;Vogel et al, 2001;Yin et al, 2003;Lovatt et al, 2005;Festa et al, 2005;Han et al, 2005;Thirumaran et al, 2006) and 1 for squamous cell carcinoma (Han et al, 2005). All articles were written in English.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%